Immunocytes interact directly with cancer cells in the tumor microenvironment: one coin with two sides and future perspectives - Ye, Zhiyi; Cheng, Pu; Huang, Qi; Hu, Jingjing; Huang, Liming; Hu, Guoming (Frontiers in Immunology, 2024)
The tumor microenvironment is closely linked to the initiation, promotion, and progression of solid tumors. Among its constitutions, immunologic cells emerge as critical players, facilitating immune evasion and tumor progression. Apart from their indirect impact on anti-tumor immunity, immunocytes directly influence neoplastic cells, either bolstering or impeding tumor advancement. However, current therapeutic modalities aimed at alleviating immunosuppression from regulatory cells on effector immune cell populations may not consistently yield satisfactory results in various solid tumors, such as breast carcinoma, colorectal cancer, etc. Therefore, this review outlines and summarizes the direct, dualistic effects of immunocytes such as T cells, innate lymphoid cells, B cells, eosinophils, and tumor-associated macrophages on tumor cells within the tumor microenvironment. The review also delves into the underlying mechanisms involved and presents the outcomes of clinical trials based on these direct effects, aiming to propose innovative and efficacious therapeutic strategies for addressing solid tumors.